Optimalisasi Media Sosial dan E-commerce sebagai Strategi Pemasaran Produk: Studi Kasus pada Toko UD Kartini - Arif Hidayat Lubis; Muhammad Hafizhan Fakhri; Zainarti Zainarti (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
The advancement of digital technology has driven Micro, Small, and Medium Enterprises (MSMEs) to adopt social media and e-commerce-based marketing strategies to expand market reach. This study analyzes the use of social media and e-commerce by Toko UD Kartini as a product marketing strategy. Using a descriptive qualitative method through interviews and observations, it was found that the store relies solely on WhatsApp, without utilizing catalog features or other platforms such as Instagram and online marketplaces. The main challenges include limited human resources and lack of promotional channel diversification. Therefore, digital development strategies such as optimizing WhatsApp Business, using social media actively, and enhancing digital marketing skills are needed to support business growth in the digital era.